VISUAL ART PRODUCTION AS TRANSITION TO SEMI-INDEPENDENT LIVING FOR PERSONS WITH INTELLECTUAL DISABILITY (Proceedings of International Conference on Special Education, 2015)
This paper offers a transition plan for persons with intellectual disability towards semi- independent living through facilitated and mentored visual art production process. Other studies in visual art activities for special needs found were in terms of fine motor skill training, expressing creative urges, building self-confidence and facilitating self-discovery, but none have purposively focused on visual art production as a transition plan for semi- independent living. Specifically, rooted on the concept of a humanistic social learning environment and a competency-based career education approach through occupational guidance and preparation, special education teaching strategies were utilized to establish the extent of visual art produced by persons with intellectual disability. The questions addressed related to whether persons with intellectual disability could produce visual artwork viable for semi-independent living. Evidence showed that scenarios of collaboration in visual art production proved effective. Recommendations emphasized the various aspects of community support for the success of persons with intellectual disability in the transition plan.